Effect of peptidoglycan amidase MSMEG_6281 on fatty acid metabolism in Mycobacterium smegmatis. (March 2020) - Miao, Jiatong; Liu, Hanrui; Qu, Yushan; Fu, Weizhe; Qi, Kangwei; Zang, Shizhu; He, Jiajia; Zhao, Shijia; Chen, Shixing; Jiang, Tao
Abstract: Mycobacterium smegmatis MSMEG_6281, a peptidoglycan (PG) amidase, is essential in maintaining cell wall integrity. To address the potential roles during the MSMEG_6281-mediated biological process, we compared proteomes from wild-type M.smegmatis and MSMEG_6281 gene knockout strain ( M.sm -ΔM_6281) using LC-MS/MS analysis. Peptide analysis revealed that 851 proteins were differentially produced with at least 1.2-fold changes, including some proteins involved in fatty acid metabolism such as acyl-CoA synthase, acyl-CoA dehydrogenase, MCE-family proteins, ATP-binding cassette (ABC) transporters, and MmpL4. Some proteins related to fatty acid degradation were enriched through protein-protein interaction analysis. Therefore, proteomic data showed that a lack of MSMEG_6281 affected fatty acid metabolism. Mycobacteria can produce diverse lipid molecules ranging from single fatty acids to highly complex mycolic acids, and mycobacterial surface-exposed lipids may impact biofilm formation. In this study, we also assessed the effects of MSMEG_6281 on biofilm phenotype using semi-quantitative and morphology analysis methods. These results found that M.sm -ΔM_6281 exhibited a delayed biofilm phenotype compared to that of the wild-type M.smegmatis, and the changes were recovered when PG amidase was rescued in a ΔM_6281::Rv3717 strain. Our results demonstrated that MSMEG_6281 impacts fatty acid metabolism and further interferes with biofilm formation. These results provide a clue to study the effects of PG amidase on mycobacterial pathogenicity. Highlights: MSMEG_6281 gene knockout strain produced a different proteomic profile compare to wild type M.smegmatis . A lack of MSMEG_6281 affects fatty acid metabolism. There was a delayed biofilm formation due to a lack of MSMEG_6281 for M.smegmatis .